1994
DOI: 10.1002/hrdq.3920050205
|View full text |Cite
|
Sign up to set email alerts
|

Workplace social networks and their relationship to student retention in on‐site ged programs

Abstract: A food‐processing corporation hosted on‐site General Educational Development (GED) programs. Despite a monetary reward for completing the time‐and‐achievement criteria established by the host corporation, student retention was low. This study suggests that on‐site program planners should address the social environment of the workplace as a factor influencing student retention in GED programs conducted in workplace locations. The research examined the workplace socialization factors that affected whether 151 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Over time, cohorts that tend to bond together become like "in-class cliques." Research indicates that students who are members of in-class cliques tend to remain in an educational program versus students who become socially isolated from others (Vann & Hinton, 1994). One of Maher's (2001) key findings with research conducted with thirteen graduate students was that the cohort setting for these students bore strong resemblance to a community, because members developed meaningful relationships and roles, and learned to "live and learn together" through both easy and difficult times (p. 8).…”
Section: Related Literaturementioning
confidence: 99%
“…Over time, cohorts that tend to bond together become like "in-class cliques." Research indicates that students who are members of in-class cliques tend to remain in an educational program versus students who become socially isolated from others (Vann & Hinton, 1994). One of Maher's (2001) key findings with research conducted with thirteen graduate students was that the cohort setting for these students bore strong resemblance to a community, because members developed meaningful relationships and roles, and learned to "live and learn together" through both easy and difficult times (p. 8).…”
Section: Related Literaturementioning
confidence: 99%
“…Candy (1991) notes that "adults are powerfully affected by aspects of their backgrounds-including family and prior education-in ways that limit and constrain their ability to be self-directing in certain learning situations" (p. 31 1). Jarvis (1987) asserts that an adult's knowledge is a sum total of his or her social experiences and that those experiences, and thus that knowledge, vary with socioeconomic class, region, and community Furthermore, adults' attitudes and behaviors, including those related to educational participation, are also impacted by socialization from nonfamily primary associations and reference groups (Bandura, 1969;Sutherland and Cressey, 1978;Vann and Hinton, 1994). Cervero and Kirkpatrick (1990) analyzed l o n g i t u h l data collected on eighteen thousand men and women who were high school seniors in 1972 and found that the likelihood of their participating in noncredit adult education at age thirty-two was related to their father's level of education, their rank in their high school class, and their attitudes toward education.…”
Section: Social Factors Related To Self-directionmentioning
confidence: 99%
“…The key finding of their report is that effective schools provide students with a supportive community. In a study of adult learners in a worksite GED program, Vann and Hinton (1994) found that 84 percent of completers belonged to class cliques, whereas 70 percent of dropouts were socially isolated. As a final example, Ashar and Skenes (1993) found in a higher education business program that by creating a social environment that motivated adult learners to persist, social integration had a significant positive effect on retention.…”
Section: Introductionmentioning
confidence: 99%